(untitled) (Communication & Society, 2019)
The current context and changes in the communicational paradigm in the last ten years lead to think we are experiencing a moment of transition that entails the end of mass media, like different studies have concluded. Among them, the most vulnerable product is the printed newspaper, which disappearance generates few doubts. However, immersed in this moment of change, we cannot yet evaluate what means to lose a journalistic model that has prevailed for over two centuries and a half as informational reference. From this perspective, the province of Cuenca, in Castile-La Mancha, one of the two in Spain which today no longer has a printed newspaper, offers us a unique scenario to approach what kind of medium positions as leader in its place. Using a mixed methodology, based on the review of documentary sources and contents analysis, we analyse a case study that aims to collect tendencies regarding proximity media. In this case, the switching from one platform to another has devaluated very relevant journalistic genres, such as the photo news or the editorial, but also some core practices in the journalism, like the editing task on the material that arriving to the editorial offices.